Pengaruh Kualitas Pelayanan dan Citra Perusahaan Terhadap Kepuasan Siswa Language Education Center (LEC) Lentera Mandiri Sukoharjo - Purwo Pebrianto; Siti Almaidah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Competition between educational institutions is a reality that cannot be ignored. Informal education service providers engaged in English language education need to implement the right competitive strategy in an effort to attract and maintain the quality of student satisfaction. The purpose of this study was to determine the effect of service quality and company image on student satisfaction. This type of research uses quantitative methods. The population of this study were students of Language Education Center (LEC) Lentera Mandiri Sukoharjo with a sample of 97 students using accidental sampling technique. Data collection using questionnaires and literature studies. The data analysis technique uses multiple linear regression with the IBM SPSS 26 application. The results showed that service quality has a significant effect on student satisfaction, where the better the service quality, the student satisfaction will also increase. Company image has a significant effect on student satisfaction, where the better the company image, the student satisfaction will also increase.